DEVELOPMENT OF EDUCATIONAL GAMES BASED ON INTERACTIVE POWERPOINT MATERIALS OF SUBSTANCES AND ITS CHANGES - Rohmatul Lailiyah; Nur Hayati (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
Learning media aims as a communication tool to convey a material in learning. Developing an Interactive PowerPoint-based Educational Game Media is one of the general objectives of this research. The development model used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). However, the Implementation phase was not carried out due to the pandemic. The data obtained are qualitative data types (from the media development process) and quantitative data (from data validation results by media experts). This research resulted in a product in the form of an interactive PowerPoint-based educational game media material substance, substance and its changes, which have been validated by several experts, namely material expert lecturers, media expert lecturers and science teachers at Al-Furqan Madrasatul Qur'an Tebuireng Jombang Middle School. With a validation score of 2.98 out of 4.00 which is categorized as valid.